Memori Kolektif dan Penyangkalan: Kasus Peristiwa Salumpaga 1919 - Setiawan, Adi (Manaqib: Jurnal Sejarah Peradaban Islam dan Humaniora, 2025)
This article presents a retrospective experiment that aims to offer a new understanding of the contestation of memory among the people of Tolitoli regarding the Salumpaga resistance movement, which took place in 1919. In addition to discussing the processes of remembering and forgetting, this article goes further by highlighting the attempts to deny the memory. This article examines how and why the Tolitoli ruling elite suppressed the memory of the Salumpaga incident in this manner. To that end, this article specifically addresses the practices of the Tolitoli authorities in treating the memories of the local community embedded in several memory sites. This article argues that the memory of the 1919 Salumpaga incident is not only contested in the context of remembering and forgetting, but also involves denial practices.